Effects of a front-seat passenger on driver attention: An electrophysiological approach. (November 2016) - Chan, Michelle; Nyazika, Simbarashe; Singhal, Anthony
Highlights: We examined the effects of a front-seat passenger on driver attention. Event-related brain potentials were collected during simulated driving. P300 was sensitive to passenger presence and driving difficulty. The presence of a passenger consumes driver resources in certain situations. Abstract: The human attention system is limited in capacity, and when performing two concurrent tasks there is competition for cognitive resources. This is particularly important in dangerous scenarios, such as driving on sharp curves where deficits in performance can be caused by various sources of distraction, including the presence of a passenger in the vehicle. In the present study, a dual-task paradigm was employed to examine the nature of attentional limits while operating a driving simulator in the presence of a passenger. The primary driving task had two levels of difficulty and event-related potentials (ERP) were collected from a secondary auditory task. In addition to several driving performance measures, our main ERP of interest was the P300. In dual-task studies, increases in primary task difficulty have been shown to reduce the amplitude of the P300 elicited by a secondary task. This presumably occurs because attentional resources initially dedicated to the secondary task are consumed by the primary task. The present results showed that compared to driving solo, the presence of a passenger was associated with a decrease in P300 amplitude in the more difficult driving conditions. These results suggest that in-car passengers may consume valuable resources in difficult driving situations that require more attentional focus in the first place.